Insecticidal activity of essential oils against Mealybug pests (Hemiptera: Pseudococcidae): A systematic review and meta-analysis - Avila, Miriam del Valle (2023)
Most mealybugs of the Pseudococcidae family are important pests of agriculture and ornamental gardens. Our aim was to perform a review and meta-analysis on 14 published scientific articles on the insecticidal activity of essential oils (EOs) against mealybug species of the Pseudococcidae family. Data on (1) species, genus, families, and plant parts from which the EO was extracted; (2) the main compounds of each EO; (3) the highest and lowest concentrations tested; and (4) the application method used for the toxicological studies was collected from each study. The metafor package (R software) was used to perform a three-level random effects meta-analysis. The families Lamiaceae, Rutaceae, Myrtaceae, Zingiberaceae and Euphorbiaceae and the genera Citrus, Cymbopogon, Syzygium, Cinnamomum and Jatropha were the most used among the studies. According to the results from the meta-analyses, 13 out of 24 genera analyzed were effective against mealybugs. All methods were effective, but fumigation and indirect contact were the most frequently used methodologies. The results obtained from the present review and meta-analysis could be used for the potential development of natural biopesticide formulations against mealybugs belonging to the Pseudococcidae family.